Diet of Conepatus chinga (Carnivore: Mephitidae) in an Polylepis forest of the Department of Arequipa, Peru - Medina, César E. (2009)
The Andean hog-nosed skunk (Conepatus chinga) is a mephitine of widely distributed in the Peruvian Andes, Almost nothing is known about the species food habits. The present study documents the diet of the Andean hog-nosed skunk in a Polylepis forest of the western slope of the Andes in southern Peru. We analyzed 226 fecal samples, which were identified by their shape and consistency. Food items are shown based on their frequency of occurrence (FO) and percentage of biomass. Diet is composed of 19 components, mainly insects (94,11%) and other invertebrates (3,27%), with occasional presence of vertebrates (1,18%) and plants (1,43%), which explains the low values of the diversity indexes (1-D= 0,16) and width of trophic niche (B= 1, H´= 0,68).